Hopfield neural network based controller for a crossbar ATM switch - Lent, Ricardo (1999)
This article describes an enhanced version of a Hopfield neural network originally proposed by Marrakchi and Troudet (1989) for large crossbar switches. We have adapted this network to control the internal flow of cells in a modern ATM crossbar switch with FIFO buffers at the input ports. The proposed model, under Self-Similar input traffic, improves the general performance of the switch.